Changes in the provision of ecosystem services based on sidewalk tree-composition scenarios - Francisco, Beatriz Lima; Bobrowski, Rogerio; Crovador Junior, Sidnei Antonio; Santos, Gabriel Alves; Santos, Jonathan Matheus; Chami, Maria Eduarda (Revista Brasileira de Ciência, Tecnologia e Inovação, 2023)
Cities have been experiencing environmental and social issues due to urban expansion processes, be them planned or not. However, several environmental solutions have been proposed and sidewalk tree planting stands out among them. The aim of the current research is to assess the process to estimate ecosystem services under different sidewalk tree composition scenarios in Irati and Curitiba cities, Paraná State. In order to do so, 10 street segments from neighborhoods sampled in city-wide inventories were selected. Information about sidewalk length, curb ramps’ width, and number of utility poles was collected for each street segment. The number of trees to be fit in each segment and sampled neighborhood was determined based on safety recommendations for these urban structures. Tree dimensions (Diameter at Breast Height - DBH, total height and crown diameter) were projected for the 55th year post-planting, based on using minimum dimensions of seedlings from small, medium and large-sized species. It was done to estimate ecosystem services in i-Tree Eco software. Significant differences among floristic composition scenarios (p<0.05) were observed for all ecosystem services in both cities. Compositions featuring large-sized species have show higher ability to provide ecosystem services, as well as higher monetary valuation, despite fitting a smaller number of trees in the assessed street segments. The herein formulated scenarios have shown the potential to increase the number of planted trees and to select compositions capable of maximizing ecosystem services’ provision and trees’ monetary value.